Efektivitas Pendidikan Kesehatan Reproduksi Berbasis Seluler pada Calon Pengantin terhadap Peningkatan Pengetahuan Kesehatan - Mayasari, Ade Tyas; Hakimi, Mohammad; Hani EN, Umu; Setyonugroho, Winny (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2020)
Background: Every individual needs to know about the issues of sexuality and reproduction before marriage so the reproduction health education is important to give to the prospective bride and groom. Technology-based education is an innovative pathway for providing health information.Objective: to determine the effectiveness of reproduction health education on the improving of knowledge of the prospective bride and groom.Method: Quasi-Experimental research with pretest posttest in Non-equivalent Control Group Design. The data were obtained from a knowledge questionnaire filled out by the prospective bride and groom. This research was conducted at KUA (the Civil Registry Office) Mlati and Gamping, Sleman Regency.Results and Discussion: There was an increase in the average posttest score of knowledge in each group. Based on the results of the data analysis, it was found that the respondents who were given reproduction health education through cellular experienced a greater increase in the post-test score (the difference between the average pretest and post-test score is 5.67) compared to the group who were not given reproduction health education via cellular (the average difference between the pretest and post-test score is 2.2). The Cellular-based reproduction health education significantly (p value = 0.00) influences the prospective bride and groom’s knowledge of the reproduction health.Conclusion: Cellular-based reproduction health education can improve the knowledge of the prospective bride and groom about the reproduction health. Keywords: Reproduction Health; Cellular; Knowledge; Premarital.